Prolonged Storage of Bound Organic Carbon in Wetland but Not Upland Soils: A 13C and 14C Perspective - Tian Ma; Yiyun Wang; Guohua Dai; Juan Jia; Zongguang Liu; Yufu Jia; Simin Wang; Erxiong Zhu; Xinying Zhang; Negar Haghipour; Lukas Wacker; Bingrui Jia; et al. (Geophysical Research Letters)
Abstract Protection by metal (hydr) oxides is one of the key mechanisms for the long‐term stabilization of soil organic carbon (SOC). However, the source and turnover of (metal‐) bound organic carbon (OC) in soils are poorly constrained. Here we present the first large‐scale study on the 13C and 14C characteristics of bound OC in 15 wetland and upland soil profiles. We find that bound OC has similar δ13C as SOC, suggesting no preference for plant‐ or microbe‐derived carbon. However, bound OC Δ14C is more negative than SOC in wetland but not upland mineral soils, and decreases with increasing reactive minerals. Hence, in contrast to the conventional assumption, bound OC is better preserved relative to SOC in wetlands with high contents of reactive metals. Our finding highlights the dynamic exchange of bound OC with SOC in upland soils and calls for a better recognition of reactive metals in stabilizing OC in wetlands.